Voltammetric Determination of Uric Acid in Clinical Serum Samples Using DMF Modified Screen Printed Carbon Electrodes - Melaku Metto; Samrawit Eramias; Bekele Gelagay; Alemayehu P. Washe (International Journal of Electrochemistry)
Screen printed carbon electrodes (SPCEs) provide attractive opportunity for sensitive and selective determination target analytes in clinical samples. The aim of the current work was to develop SPCEs based sensor for the determination of uric acid in clinical serum samples. The electrodes were pretreated by soaking in N,N-dimethylformamide for 5 minutes followed by drying in an oven at 100°C for 20 mins. The effect of surface pretreatment was characterized using cyclic voltammetry. The current response of uric acid detection was improved by a factor of 3.5 in differential pulse voltammetric measurement compared to unmodified electrode. Under the optimized conditions, the sensor displayed two dynamic linear ranges 5-100 μM and 100-500 μM with correlation coefficient, R2, values of 0.98782 and 0.97876, respectively. The limit of detection and limit of quantification calculated using the dynamic linear range 5-100 μM were 1.9 x 10−7 M and 6.33 x 10−7 M, respectively. The developed sensor displayed well separated and discerned peaks for UA in presence of the potential interferent (ascorbic acid and citric acid). The electrode was successfully applied for the detection of very low level of UA in clinical serum samples in a phosphate buffer solution (pH = 7). The proposed sensor showed a very high reproducibility and repeatability with the relative standard deviation of 0.9%. In conclusion, a simple and low cost sensor based on SPCEs is developed for sensitive and selective detection of uric acid in clinical samples.